Ho Chi Minh’s Ideology on revolutionary Medical Ethics - Hieu, Le Thi Tam (The journal of contemporary issues in business and government, 2021)
President Ho Chi Minh, a hero of national liberation, a world cultural celebrity has left us a huge and extremely valuable spiritual legacy, which we have not been able to exploit the full extent of that heritage in both breadth and depth, including his ideology on medical ethics. Researching on his medical ethics is important in improving the medical ethics of Vietnamese doctors today. The author uses the method of analysis, synthesis, and comparison of data sources to study Ho Chi Minh’s ideology on medical ethics. The research results show that Ho Chi Minh’s ideology on medical ethics shows the unity between morality and politics - a characteristic in Ho Chi Minh’s ideology, which is the revolutionary medical ethics in general and the medical ethics of the socialist doctor, including ethical standards to regulate the perception and behavior of doctors in relation to patients, profession, colleagues, society and themselves.